2023
DOI: 10.1038/s41598-023-43718-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced structural integrity of Laser Powder Bed Fusion based AlSi10Mg parts by attaining defect free melt pool formations

M. Saravana Kumar,
Che-Hua Yang,
Muhammad Umar Farooq
et al.

Abstract: This research aims to fabricate an AlSi10Mg parts using Laser Powder Bed Fusion technique with enhanced structural integrity. The prime novelty of this research work is eliminating the balling and sparring effects, keyhole and cavity formation by attaining effective melt pool formation. Modelling of the Laser Powder Bed Fusion process parameters such as Laser power, scanning speed, layer thickness and hatch spacing is carried out through Complex Proportional Assessment technique to optimize the parts' surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…BBD employed in this study follows a three-level factorial design approach, where the factors under investigation are examined at low, medium, and high levels 67 , 68 . This design is constructed using a series of points that form a three-level factorial design, which is then augmented with additional points forming a central composite design.…”
Section: Methodsmentioning
confidence: 99%
“…BBD employed in this study follows a three-level factorial design approach, where the factors under investigation are examined at low, medium, and high levels 67 , 68 . This design is constructed using a series of points that form a three-level factorial design, which is then augmented with additional points forming a central composite design.…”
Section: Methodsmentioning
confidence: 99%
“…Chu [ 21 ] confirmed that coarser powders are much more sensitive to changes in laser power in terms of melt pool characteristics, defect population, and size, showing significant improvements in relative density upon increasing laser power. Kumar [ 22 ] obtained optimal process parameters such as laser power, scanning speed, layer thickness, and hatch spacing, improving the structural integrity of the printed AlSi10Mg parts. Chen [ 23 ] proposed a novel approach in order to reduce defects, refine grains, and enhance hardness during the LPBF process, utilizing low laser power and a continuous scanning strategy.…”
Section: Introductionmentioning
confidence: 99%
“…One of the common defects observed in metallic components subjected to fatigue loading during service is cracking [18,19]. These cracks cannot simply be filled with additive feedstock material.…”
Section: Introductionmentioning
confidence: 99%